Equation to predict the 137Cs leaching dynamic from evergreen canopies after a radio-cesium deposit. (September 2015) - Loffredo, Nicolas; Onda, Yuichi; Hurtevent, Pierre; Coppin, Frédéric
Abstract: The Fukushima Daiishi nuclear power plant (FDNPP) accident led to a massive radionuclide deposition mainly onto Japanese forest canopies. In our previous study, an improved double exponential (IDE) equation including rainfall intensity was proposed to estimate the 137 Cs hydrological transport from evergreen canopies to the ground. This equation used two types of parameters, kinetic ( k 1 and k 2 ) and leachable stock ( A 1 and A 2 ). Those parameters have been estimated by adjusting them in the IDE equation in order to accurately describe the measured cumulative leached 137 Cs from canopies ( k 1  = 4.2E-04–5.0E-04 d −1, k 2  = 1.2E-02–1.7E-02 d −1, A1  = 62–99 kBq/m 2, A2  = 25–61 kBq/m 2 ). In this study, we linked the total leachable stock ( A leachable, a parameter of the IDE equation corresponding to A 1  +  A 2 ) to a physiological criteria (the canopy closure CC, which can be measured with a simple camera equipped with a fish-eye objective). Furthermore, the kinetic parameters measured for Japanese cedar ( k 1  = 5.0E-04 d −1, k 2  = 1.2E-02 d −1, and r 12  = 0.22 ( r 12  =  A 1 / A 2 ) could also be used for two other coniferous species: Japanese cypress and spruce. This suggests that these parameters could be constants for coniferous forests. Highlights: A double exponential equation including rainfall intensity was used to model leachable cesium loss from cedar canopies. This equation used two types of parameters, kinetic ( k 1 and k 2 ) and leachable stock ( A 1 and A 2 ). We linked the leachable stock to the canopy structure (canopy closure). The kinetic parameters were similar for different evergreen stands after Chernobyl and Fukushima accident. We propose an equation for predicting the leachable cesium dynamic in different evergreen species.